Butterfly Graft Technique for Addressing the Internal Nasal Valve - Varman, Rahul; Clark, Madison (Facial Plastic Surgery, 2022)
Nasal airway obstruction is a common presenting complaint to otolaryngology clinics, with the internal valve a commonly implicated anatomic area of obstruction. The nasal butterfly graft is a robust technique to address this subsite with good reported functional and aesthetic outcomes in both primary and secondary rhinoplasty. We describe our approach to patient evaluation, surgical candidate selection, operative technique, and outcomes assessment for this technique.
Keywords: butterfly graft; rhinoplasty; nasal obstruction; internal nasal valve; conchal cartilage